Balinese Congklak Games, Maciwa, to Improve the Development of Symbolic Thinking in Early Childhood - Putu Indah Lestari; Elizabeth Prima (LPPM Universitas Pahlawan Tuanku Tambusai, 2019)
This study aimed to determine the implementation of the Balinese congklak game (maciwa) in improving the development of early childhood symbolic thinking. This research was carried out in B1 TK Alit Kirana children in the academic year 2018/2019. This research design was Classroom Action Research using the observation method. The subjects of this classroom action research were 18 students of Group B1 TK Alit Kirana consisting of 10 males and 8 females. The objective of this research was the implementation of the Balinese congklak (maciwa) game to improve the development of symbolic thinking in early childhood. The results obtained in Cycle I showed that, 66.67% had achieved mastery learning, in Cycle II showed that 88.89% had achieved learning completeness. There was an improvement in the development of child symbolic thinking by 22.22% from Cycle I to Cycle II. This means that the implementation of the Balinese congklak game (maciwa) could improve the development of children's symbolic thinking. The Balinese congklak game can be piloted in other areas of development skill in early childhood education